Robust temporal optimisation for a crop planning problem under climate change uncertainty. (2022) - Randall, M.; Montgomery, J.; Lewis, A.
Abstract: Considering a temporal dimension allows for the delivery of rolling solutions to complex real-world problems. Moving forward in time brings uncertainty, and large margins for potential error in solutions. For the multi-year crop planning problem, the largest uncertainty is how the climate will change over coming decades. The innovation this paper presents are novel methods that allow the solver to produce feasible solutions under all climate models tested, simultaneously. Three new measures of robustness are introduced and evaluated. The highly robust solutions are shown to vary little across different climate change projections, maintaining consistent net revenue and environmental flow deficits. Highlights: Temporal optimisation is extended with novel robust techniques. Agricultural planning over long time horizons factor in climate change models. Crop planting solutions' profits vary minimally across climate change model. Results indicate agricultural land use must change in medium and long term.